Cotton-Mouton effect using algebraic diagrammatic construction schemes in the intermediate state representation formalism - Schneider, Friederike; Papapostolou, Antonia; Leitner, Jonas; Rehn, Dirk R.; Dreuw, Andreas (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2023)
The Cotton-Mouton effect is theoretically investigated for a selected set of molecules by using a novel computational methodology based on algebraic diagrammatic construction (ADC) schemes in the intermediate state representation (ISR) formulation. Therefore, the electronic contributions to the frequency-dependent polarizabilities and, for the first time, to the magnetizabilities as well as mixed electric and magnetic hypermagnetizabilities have been computed in the ADC/ISR framework. In addition to calculation of the Cotton-Mouton constant and the birefringence, the gauge origin dependence of the computed tensors and the applied methodology are thoroughly investigated. The new ADC/ISR methodology, employing the recently presented responsefun package, is applied to a test set of Ne and small molecules (H2, HF, O2, CO2, and benzene) and compared to data from the experiment as well as other ab initio methods. The presented theoretical ab initio ADC/ISR approach is a substantial extension of the available computational methods for the investigation of complex nonlinear properties, however, with a gauge origin dependence inherent to the method that decreases with increasing perturbation order.
Online veröffentlicht: 10. Oktober 2023
Gesehen am 15.12.2023